Colorimetric and fluorometric dual-mode detection of aniline pollutants based on spiropyran derivatives. Issue 86 (2nd September 2016) - Tian, Weiguo; Xue, Yinan; Tian, Jintao; Gong, Peizhen; Dai, Jinhui; Wang, Xin; Zhu, Zhibin
Abstract : The selective UV-vis absorption of spiropyran and the fluorescence quenching of SP-cellulose material induced by aniline were observed and exploited for rapid detection and accurate quantitative determination of aniline pollutants in the environment. Abstract : The selective UV-vis absorption of spiropyran (SP) and the fluorescence quenching of a SP-cellulose material induced by aniline were observed in this study, which were exploited for rapid detection and accurate quantitative determination of aniline pollutants in the environment. The concentration of aniline pollutants can be rapidly evaluated by the naked eye in a colorimetric and fluorometric dual-mode by the SP-cellulose test paper. Furthermore, the aniline pollutants can also be accurately determined using the above materials with the aid of portable spectrophotometers. The detection processes are effective, low cost and easy to operate, and do not require personnel with expertise or cumbersome equipment, and are therefore especially suitable for real-time-field monitoring of aniline pollutants outdoors.